The Effect of Dengue Cards Game Media Education on Dengue Knowledge and Prevention of DHF in Grade 7 Students at SMPN 2 Kupang Timur - Risel Idwan Ataupah; Jane Leo Mangi; Yoani M.V.B Aty; Fitri Handayani (Poltekkes Kemenkes Kupang, 2025)
Dengue Hemorrhagic Fever (DHF) remains a major public health problem in Indonesia, with high morbidity and mortality rates occurring annually. One contributing factor to the increasing number of cases is the lack of knowledge among school-aged children regarding dengue prevention. To address this issue, educational interventions using interactive and engaging media such as the Dengue Cards Game have been developed to improve students’ understanding and preventive behavior toward DHF. This study aimed to determine the effect of health education using the Dengue Cards Game on students’ knowledge and dengue prevention behavior at SMPN 2 Kupang Timur. Employing a quantitative approach with a pre-experimental one group pre-test post-test design, the study involved 34 students selected through purposive sampling. A 17-item questionnaire was used to assess knowledge and preventive behavior, and data were analyzed using the non-parametric Wilcoxon Signed Ranks Test. The results showed a significant improvement in students’ knowledge and dengue prevention behavior after the intervention, with a p-value of 0.000 (< 0.05). Prior to the education session, most students had a moderate level of knowledge (67.6%), which increased to a good level (91.2%) afterward. Therefore, the Dengue Cards Game is proven effective as an innovative and engaging educational tool to enhance students’ knowledge and preventive behavior regarding dengue fever.